PENGARUH PREDICTORS OF ONLINE SEARCH INTENTION TERHADAP INTENTION TO USE INTERNET FOR PURCHASE MELALUI INTENTION TO USE INTERNET FOR INFORMATION SEARCH PADA USER KASKUS DI SURABAYA - DWINANDA, GILANG ANDHIKA (Kajian Ilmiah Mahasiswa Manajemen, 2012)
The aim of this research is to analyze the effect of utilitarian value of Internet information search, hedonic value of Internet information search, perceived benefit of Internet shopping, perceived risk of Internet shopping, purchase experience, against intention to use Internet for information search for online shop at www.kaskus.co.id. In addition researcher also wants to know the influence of intention to use Internet for information search against intention to use the Internet for purchase at online shop on www.kaskus.co.id. Research design of this study is causal research that can explain the causality of independent variable towards dependent variable. Variable in this case is latent exogenous, there are: utilitarian value of Internet information search, hedonic value of Internet information search, perceived benefit of Internet shopping, perceived risk of Internet shopping, and purchase experience. Whereas latent endogenous (dependent variable) is: intention to use Internet for information search and intention to use the Internet for purchase. The total number of research samples is a hundred and fifty samples. Analysis technique or methods of this research uses structural equation models with LISREL program. The result shows that utilitarian value of Internet information search, hedonic value of Internet information search, perceived benefit of Internet shopping, and perceived risk of Internet shopping, purchase experience affected toward intention to use Internet for information search at online shop on www.kaskus.co.id. Intention to use Internet for information search affected toward intention to use the Internet for purchase at online shop on www.kaskus.co.id. Intention to use Internet for information search being able to strengthen the influence of independent variable towards purchase intention.